Catalogue of the Arabic, Persian, and Turkish Manuscripts of the Yahuda Collection of the National Library of Israel Volume 2 - Wust, Efraim (Islamic Manuscripts and Books, 2020)
The Yahuda Collection was bequeathed to the National Library of Israel by one of the twentieth century's most knowledgeable and important collectors, Abraham Shalom Yahuda (d. 1951). The rich and multifaceted collection of 1,186 manuscripts, spanning ten centuries, includes works representing the major Islamic disciplines and literary traditions. Highlights include illuminated manuscripts from Mamluk, Mughal, and Ottoman court libraries; rare, early copies of medieval scholarly treatises; and early modern autograph copies. In this groundbreaking Arabic catalogue, Efraim Wust synthesizes the Islamic and Western manuscript traditions to enrich our understanding of the manuscripts and their compositions. His combined treatment of Arabic, Persian, and Turkish manuscripts preserves the integrity of the collection and honors the multicultural history of the Islamic intellectual traditions.